Polymorphism at the bovine tumor necrosis factor alpha locus and assignment to BTA 23 - Agaba, Morris; Kemp, Stephen J.; Barendse, W.; Teale, A.J. (Springer, 1996)
Four single-strand conformation variants of the bovine tumor necrosis factor alpha gene by analysis of PCR-amplified fragments were identified. The variants are inherited in Mendelian fashion and are informative for linkage mapping. We have mapped the bovine gene to Chromosome (Chr) 23 in a panel of somatic cell hybrids and observed genetic linkage to the major histocompatibility complex (BoLA) genes and microsatellite markers on bovine Chr 23 in an internatonal bovine reference family panel. The distribution of the alleles was determined in cattle of different breeds and of different geographical origins, which included trypano-susceptible and trypano-tolerant cattle.